Pengembangan Wisata di Desa Hargorejo, Kecamatan Kokap, Kabupaten Kulon Progo, Daerah Istimewa Yogyakarta - Lukisworo, Agustinus Aryo (Jurnal Atma Inovasia, 2022)
Kuliah Kerja Nyata (KKN) Periode 79 of Universitas Atma Jaya Yogyakarta from April to May 2021, was carried out through online mode. This was due to the Covid-19 pandemic spread prevention in Indonesia. Within this period, the third group of A Unit was assigned to the Hargorejo Village, Kokap, Kulon Progo, Daerah Istimewa Yogyakarta. All of the third group KKN programs were drafted upon secondary data that obtained by online inquiries. The findings show that Hargorejo Village has a promising tourism potency to develop, namely Gunung Kuniran. In this location, aside with tourist attraction, there are also plantation and cultural arts resources that could be optimized to support the development of the tourism potency. Based on SWOT analysis of the existing condition, there are three program that should be done to develop the Gunung Kuniran tourism potency, that are agro-tourism development, arts performance stage renovation, and public facility refinement. Hopefully the Gunung Kuniran tourism development will lead to the economic development of Hargorejo Village.